PENERAPAN MEDIA INTERAKTIF DALAM PEMBELAJARAN MATEMATIKA - Rafik Asril (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2022)
This study aims to analyze the ability of teachers to develop interactive learning media and also to analyze the usefulness of interactive media in learning mathematics. The subjects of the study included two seventh grade mathematics teachers and six seventh grade students of SMP Muhammadiyah 08 Batu. The method used in this research is a descriptive field method with a case study approach. While the research instruments used include documentation; observations, and interviews. The results of this study indicate that mathematics teachers are able to develop interactive media, but the resulting media is still relatively simple. In addition, the results of this study also show that the use of interactive media in learning mathematics can provide benefits.